Review of the genus Typhloiulus Latzel, 1884 in the Dinaric region, with a description of four new species and the first description of the male of Typhloiulus insularis Strasser, 1938 (Diplopoda: Julida: Julidae) - Antić, Dragan Ž.; Dražina, Tvrtko; Rađa, Tonći; Lučić, Luka R.; Makarov, Slobodan E. (Zootaxa, 2018)
A review of the genus Typhloiulus Latzel, 1884 (Julida: Julidae) in the Dinaric region is given. Previously published and new faunistic records are provided for each species, together with notes for some of them. Four new species are described: T. clavatus sp. nov., T. gracilis sp. nov., T. opisthonodus sp. nov., and T. parvulus sp. nov., all from caves in Dalmatia and Herzegovina. In addition, we provide the first description of the male of T. insularis Strasser, 1938. Some taxonomic relationships among Typhloiulus species and biogeographical aspects (with distribution maps) of the genus are discussed.